2021
DOI: 10.3390/cells10123424
|View full text |Cite|
|
Sign up to set email alerts
|

Geniposide Ameliorated Dexamethasone-Induced Cholesterol Accumulation in Osteoblasts by Mediating the GLP-1R/ABCA1 Axis

Abstract: Background: Overexposure to glucocorticoid (GC) produces various clinical complications, including osteoporosis (OP), dyslipidemia, and hypercholesterolemia. Geniposide (GEN) is a natural iridoid compound isolated from Eucommia ulmoides. Our previous study found that GEN could alleviate dexamethasone (DEX)-induced differentiation inhibition of MC3T3-E1 cells. However, whether GEN protected against Dex-induced cholesterol accumulation in osteoblasts was still unclear. Methods: DEX was used to induce rat OP. Mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Studies have also confirmed that wogonin may have beneficial effects in ameliorating dyslipidemia via PPAR α activation. Furthermore, other compounds of HLJDD also have the function of regulating dyslipidemia, such as crocetin [ 30 ], baicalein [ 31 ], and geniposide [ 32 ]. Together, they form a network that embodies the multicompound role of the TCM decoction in regulating dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also confirmed that wogonin may have beneficial effects in ameliorating dyslipidemia via PPAR α activation. Furthermore, other compounds of HLJDD also have the function of regulating dyslipidemia, such as crocetin [ 30 ], baicalein [ 31 ], and geniposide [ 32 ]. Together, they form a network that embodies the multicompound role of the TCM decoction in regulating dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…Both osteoblasts and adipocytes are differentiated from BMSCs. Glucocorticoid-induced lipid accumulation has been demonstrated to be negative to bone mass ( Zheng et al, 2021 ). It is evident that bone loss increases with ageing.…”
Section: The Protective Activity Of Genistein Against Bone and Cartil...mentioning
confidence: 99%
“…In addition, geniposide ameliorated DEX-induced cholesterol accumulation in MC3T3-E1 cells and inhibited cell differentiation through modulating the GLP-1R/ABCA1 axis. Moreover, geniposide improved DEX-induced OP by activating GLP-1R expression in vivo and in vitro [ 35 ]. In addition, geniposide has the function of anti-skeletal muscle fibrosis.…”
Section: Effect Of Geniposide On Osteoporosismentioning
confidence: 99%